Studi Kualitas Air Minum Isi Ulang Di Jalan Abdul Kadir Kecamatan Tamalate Kota Makassar - Hasan hasan (Jurnal Media Laboran, 2016)
Water Recharging is one of the new altenative, cheaper and more practical for the community, to meet the drinking water needs. However Drinking Water Quality Recharging can cause health problems relating to the quality parameters of physical, chemical, biological and radioactive. The purpose of this study was to determine the quality of drinking water Recharging based processing, parameter temperature Substances, Smell, Taste, iron, pH, and MPN Coli. This study uses descriptive and observational approach sampling method is total sampling with a sample size 6 samples. The results showed that the treatment process AMIU, temperature parameters 27.0 to 29.1, Keruhan 0.0 to 18 NTU, Colour all TCU 0, Total Dissolved Substance 20-300 mg/L, smell all odorless, tasteless Rasa all, a pH of 7.50 to 8.11 mg / L, Iron all O mg/L for all depot qualify. Coli MPN biological parameters that five samples grading qualify 0/100 MI water samples and one sample that does not qualify the 70/100 level MI of water samples by PERMENKES No 492/Menkes PER / IV/ 2010 levels 0/100 ml sample Based on the research that has been conducted, it is expected that all employers Depot Refill Water to keep improving the quality of refill drinking water produced and To intansi re ated to always perform continuous monitoring of the quality of drinking water refills will distributorkan to the public. And to society as a consumer to always be cautious in choosing and consuming drinking water refils.